Response and Coping on Physically to Side Effect Cemotherapy in Women Suffered Cervical Cancer - Winarsih Nur Ambarwati; Erlinda Kusuma Wardani (Jurnal Ners, 2015)
Introduction: The Cervical cancer is a cancer that causes most deaths especially in developing countries. The management for most cancer is chemotherapy. Chemotherapy has many impacts in many areas of life, among others, the impact lays on the physical and psychological. Lack of information about the side effects of chemotherapy treatments cause the quality of life of patients continued to decline. The Objective of the research: It: is to develop the concept of responses and coping physically of the cervical cancer patients who received the chemotherapy. Methods: The study design was designed using qualitative methods. The approach used was qualitative research of the Phenomenology Study. The subjects of the research were the women with cervical cancer treated by chemotherapy in Hospital of Dr. Moewardi of Surakarta. The sampling technique was the purposive sampling. The research instruments were interview guidelines, observation guidelines, stationery and recording devices, and fi eld notes. The data analysis would be conducted by using qualitative analysis.Result: The physical response of cervical cancer patients on chemotherapy include nausea, vomiting, constipation, peripheral neuropathy, fatigue, weight loss, alopecia, skin toxicity, decreased appetite, pain, change in taste on the tongue. The coping of the patients generally use traditional ways or leave it, and very few pharmacological were used to resolve the problem.Conclusion: Chemotherapy give real effect to the physical. Patients in general were coping by traditional and non-pharmacological means. Suggestion: the results of the research can be used as evidence-based research in the treatment of cervical cancer patients with chemotherapy and used as the basis for the development of interventions to improve the life quality of the patients.